Analysis of Students' Difficulties in Solving Physics Problems with Multiple Representation Using What's Another Way Method - Misbahul Jannah; Muhammad Nasir; Desy Shafira Siahaan; Soewarno Soewarno (STAI Hubbulwathan Duri, 2022)
Based on the observations that had been made, students experienced some difficulties in solving physics problems, especially in multiple representations. They had a problem in applying a concept with a different form of representation from the previous representation. To overcome this, it is necessary to apply what's another way method as solving problem solution. This study aims to analyze the student’s difficulties in solving physics problems with multiple representations using what's another way method on heat and temperature topics in a private islamic senior high school located in Banda Aceh. The design of this study was qualitative descriptive research with five students as subjects. The instruments used were test questions and interviews, then the results of the data were analyzed using what's another way method. The results showed that all students experienced difficulties at level II (planning problem solving), level III (problem solving), level IV (re-checking), and level V (reflection), while for difficulty level I, namely understanding the problem, it is found that no one face the problem. Therefore, the difficulties of students can be grouped into indicators of difficulty in applying the principles and difficulties in solving verbal problems. The factors cause these difficulties may occur due to error in using formulas, error in mathematical calculations, error in unit conversions, error in symbols writing , and error in double-checking.